Hubungan antara tekanan kerja dan kesihatan mental dalam kalangan guru sekolah - Nur Aishah Mohd Yahaya Khan,; Shahlan Surat, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Nowadays, the various changes that have taken place in the education system in Malaysia have had an impact on the mental well-being among teachers. This situation can be seen as there is an increase in the number of teachers who choose to retire early because they are burdened with pressure involving their work as an educator. In this connection, the study was conducted to identify the level of stress in the work of teachers and the mental health of school teachers. The study was also conducted to find out about the correlation between work stress and mental health among schoolteachers. This study applies the design of quantitative methods and uses survey questions as a study instrument. Respondents of this study involved 50 people consisting of school teachers in the Seberang Perai Tengah district of Penang. The results of the study found that the teacher's work stress level was at a low stress level. Whereas for mental health, depression records low levels, anxiety records low average levels, and stress also records low moderate levels. For the correlation found there is a significant link between work stress and mental health among school teachers. It is hoped that the findings of this study will contribute scientifically to addressing the stress of work among teachers in Malaysia.